Community Awareness towards Inclusive Education for Children with Learning Disabilities in Myanmar Educational Context - Lum Pan; Thea Czaireena T. Dizon (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Although Myanmar has adopted an international legal framework through the Education Law (2007) and the Child Rights Law (2019), significant gaps exist between formal policies and practical implementation. Public awareness is still hampered by negative stigma, infrastructure constraints, and the influence of certain cultural and religious beliefs that contribute to the exclusion of children with learning disabilities. This literature review aims to explore the level of public awareness of inclusive education for children with learning disabilities in Myanmar and identify factors that hinder the transition from policy to practical inclusion. This study used a literature review method by analyzing various policy documents, previous studies, and reports on the educational context in Myanmar, including its impact on ethnic minority groups and children with disabilities. Findings indicate that the main challenges to inclusion in Myanmar include sociocultural factors such as the concept of